Poetics of the Gaze: Idea of the Journey in the chronicles of Martín Caparrós (Anclajes, 2021)
Contemplating the journey occupies a central role in the work of Martín Caparrós. In this article, I analyze how two related problems affecting the journey narrative in Larga distancia and El interior, by Martín Caparrós, are solved. The first problem is the apparent paradox assumed in theories about the cancelation of experience in the journey narrative. The second is the language used to narrate the journey. Ultimately, I intend to extract a poetics of the gaze from Martín Caparrós’s reflections on the journey.
Keywords: Argentine literature; Martín Caparrós; journey narrative; chronicle